An introduction to sixteenth-century French literature and thought : other times, other places - Kenny, Neil (New readings (London, England), 2008)
"The age of Shakespeare, Cervantes, Erasmus, Luther and Machiavelli produced in France too some of Europe's greatest ever literature and thought: Montaigne's Essays, Rabelais's comic fictions, Ronsard's poetry, Calvin's theology. These and numerous other extraordinary writings emerged from and contributed to cultural upheavals: the movement usually known as the Renaissance, which sought to revive ancient Greek and Roman culture for present-day purposes; religious reform, including the previously unthinkable rejection of Catholicism by many in the Reformation, culminating in decades of civil war in France; the French language's transformation into an instrument for advanced abstract thought